2017
DOI: 10.1371/journal.pntd.0005815
|View full text |Cite
|
Sign up to set email alerts
|

Increased level and interferon-γ production of circulating natural killer cells in patients with scrub typhus

Abstract: BackgroundNatural killer (NK) cells are essential immune cells against several pathogens. Not much is known regarding the roll of NK cells in Orientia tsutsugamushi infection. Thus, this study aims to determine the level, function, and clinical relevance of NK cells in patients with scrub typhus.Methodology/Principal findingsThis study enrolled fifty-six scrub typhus patients and 56 health controls (HCs). The patients were divided into subgroups according to their disease severity. A flow cytometry measured NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Whereas at 24 h HLA-ABC and ␤2M chain amounts were slightly lower in O. tsutsugamushi-infected cells than in uninfected cells, by 72 h they had significantly decreased by 74% and 65%, respectively. Gamma interferon (IFN-␥), a cytokine whose levels are elevated during O. tsutsugamushi infection of humans and mice, can stimulate expression of MHC-I components (1, [34][35][36][37][38]. Even in the presence of IFN-␥, the bacterium pronouncedly reduced the cellular levels of HLA-ABC and ␤2M.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas at 24 h HLA-ABC and ␤2M chain amounts were slightly lower in O. tsutsugamushi-infected cells than in uninfected cells, by 72 h they had significantly decreased by 74% and 65%, respectively. Gamma interferon (IFN-␥), a cytokine whose levels are elevated during O. tsutsugamushi infection of humans and mice, can stimulate expression of MHC-I components (1, [34][35][36][37][38]. Even in the presence of IFN-␥, the bacterium pronouncedly reduced the cellular levels of HLA-ABC and ␤2M.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of CD11c and CD69 on this peripheral cell subset is very intriguing, as these two markers are normally detected to a higher degree in tissue-resident NK cells (54,55). In addition, it has been shown that CD69 + NK cells expressed IFN-γ to a higher degree than CD69 − NK cells (56). A higher frequency of activated NK cells with a pro-inflammatory phenotype in adults with newly diagnosed T1D might reflect the ongoing inflammatory process, as this alteration was not observed in samples from patients with L-T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this result, dominance of Th1-biased immune responses, as represented by elevated IFN-γ ( Figure 3 ), has also been observed in scrub typhus patients. 36 , 37 In summary, cellular immunity mediated by antigen-specific T cells may have a significant role in the eradication of bacterial pathogens from infected patients. ScaA- or TSA56-specific T cells, however, rapidly declined at 1 year after infection and were barely detectable at 2 years after recovery.…”
Section: Discussionmentioning
confidence: 99%